Statistical challenges of stress test financial stability assessments - Paul H. Kupiec (American Enterprise Institute (AEI), 2020)
Banking system stress tests are a key component of IMF/World Bank financial stability assessments.
Keywords: A; 330; Bank Regulation; Banking Crisis; Financial Stability; Macroeconomics; Monetary Policy; Stress Tests